Tinjauan Yuridis Terhadap Hak Imunitas Organisasi Internasional dalam Pertanggungjawaban atas Pelanggaran Hukum Internasional - Adela Sahla (Jaksa : Jurnal Kajian Ilmu Hukum dan Politik, 2024)
International Organization is an association consisting of countries that formed based on the main instrument to achieve common goals through activities carried out in it. In addition to countries that hold the main position as the subject of international law, international organizations also have legal personalities that enable them to take legal actions and hold rights and obligations. To achieve its objectives, international organizations such as the United Nations shall enjoy immunity and privilege in the territory of its Members. Moreover, representatives of members and employees of the United Nations can exercise their functions independently as regulated in Article 105 of the United Nations Charter. In spite of that, international organizations can take actions that are contrary to international law. The existence of an internationally wrongful act requires an international organization to provide reparation, such as restitution, compensation, satisfaction, and interest. The purpose of this research is to find out how far the regulation of immunity rights owned by international organizations is and how it is applied in practices that cause violations of international law. The research method used is normative legal research conducted by analyzing the literature related to the topic. As a result of this research, the author concludes that there are no international legal provisions that provide limitations on immunities. In addition, the current regulation creates inconsistencies in the application of immunities in some countries considering that there are some countries that apply it absolutely and some other countries apply it functionally.